Leaf carbon isotope discrimination and vegetative responses of Dryas octopetala to temperature and water manipulations in a High Arctic polar semi-desert, Svalbard - Welker, Jeffery M; Wookey, Philip; Parsons, Andrew N; Press, Malcolm C; Callaghan, Terry V; Lee, John A (Oecologia, 1993)
Integrative ecophysiological and vegetative responses of Dryas octopetala were measured in response to field perturbations of temperature, precipitation and their interactions in a polar semi-desert in Svalbard, Norway (79°N, 12°E). Leaf carbon isotope discrimination (Δ), total leaf nitrogen concentration and leaf development were determined for photosynthetic leaves collected during the last week of August 1991, after one season of manipulations. Individual leaf weight and the total mass of leaf tissue were significantly lower when water was added, irrespective of temperature regime. Leaf carbon isotope discrimination and estimated long-term ci/cavalues (the ratio of CO2 concentration in leaf intercellular spaces to that in the atmosphere) were significantly higher under all three field manipulation treatments, and Δ was significantly reduced when Dryas was grown under drought conditions in a related greenhouse study. Nitrogen concentrations of plants from the field experiment were significantly lower under warmed conditions regardless of water regime. Our results indicate that changes in environmental conditions in high arctic settings will result in alterations of Dryas leaf gas exchange, as expressed by increases in carbon isotope discrimination, which may be accompanied by shifts in leaf nitrogen content and leaf biomass. © 1993 Springer-Verlag.